An Overview: Laboratory Safety and work Practices in Infectious Disease Research - Shivaji K Jadhav (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2018)
Occupational exposure and risk of acquiring the infections is a very serious issue and it plays an important role concerned to personnel safety in the laboratory. It is very much essential to emphasis on safety aspects for each personnel working in infectious laboratories. This review article provides an insight on bio safety practices to be followed for safe and effective functioning of the laboratory to prevent the occupational exposure.